Atomic layer etching technique for InAlN/GaN heterostructure with AlN etch-stop layer. (1st June 2022) - Du, Fangzhou; Jiang, Yang; Qiao, Zepeng; Wu, Zhanxia; Tang, Chuying; He, Jiaqi; Zhou, Guangnan; Cheng, Wei-Chih; Tang, Xinyi; Wang, Qing; Yu, Hongyu
Abstract: An atomic layer etching (ALE) technique for InAlN/AlN/GaN structure was investigated for the first time. Different recipes with O2 modification times of 30–180 s and BCl3 removal RF powers of 15–25 W were tested. For three optimized recipes—30 s O2 + 15 W BCl3 ALE, 90 s O2 + 20 W BCl3 ALE, and 180 s O2 + 25 W BCl3 ALE—with increasing RF power, the etching per cycle increased from 0.14 to 1.00 nm/cycle. At the same time, the surface root-mean-square roughness remained approximately 0.28 nm and was thus much lower than that of the as-grown InAlN surface (0.45 nm) and the surface obtained by the conventional BCl3 dry etching approach (0.69 nm). Atomic force microscopy, X-ray photoelectron spectroscopy, and scanning transmission electron microscopy with energy dispersive X-ray spectroscopy measurements demonstrated the etch-stop effect and verified that the under-etching ALE technique was the most efficient way to precisely control the InAlN etching depth and surface morphology. This finding has important implications for realizing high-performance InAlN/GaN high electron mobility transistors.